2022
DOI: 10.3390/metabo12040335
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Serum Metabolome in Elite Cross-Country Skiers: A Controlled Study

Abstract: Exercise has been shown to affect gut the microbiome and metabolic health, with athletes typically displaying a higher microbial diversity. However, research on the gut microbiota and systemic metabolism in elite athletes remains scarce. In this study, we compared the gut microbiota profiles and serum metabolome of national team cross-country skiers at the end of an exhausting training and competitive season to those of normally physically-active controls. The gut microbiota were analyzed using 16S rRNA amplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…inactive participants 36,38,63,66,6871,78,84,85,39,41,42,4446,48,59 ( Table 2 ). Sixteen studies found significant differences in microbial diversity 47,49,62,7476,79,80,51,52,5458,61 and 13 in the abundance of specific microbial taxa 47,52,78,79,104,53,5558,7476 between athletes vs . non-athletes, professional vs .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…inactive participants 36,38,63,66,6871,78,84,85,39,41,42,4446,48,59 ( Table 2 ). Sixteen studies found significant differences in microbial diversity 47,49,62,7476,79,80,51,52,5458,61 and 13 in the abundance of specific microbial taxa 47,52,78,79,104,53,5558,7476 between athletes vs . non-athletes, professional vs .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies analyzed the gut microbiome, with the exception of ten which collected saliva, oral, oropharyngeal, muscle, blood or vaginal samples 36,43,52,64,80,86,88,102,113,116 ( Table 2 ). Concerning the detection method, 78 studies conducted the 16S rRNA gene sequencing approach to characterize the microbiome 23,36,45–48,5153,55,56,58,37,5964,6669,38,7079,39,8087,90,91,40,9295,97100,102,103,41,104,105,107113,115,42,116,118121,123125,43,44 , 16 performed metagenomics analyses 23,49,101,106,114,115,117,122,50,54,57,60,65,89,95,96 and two studies focused on meta-transcriptomics (i.e., microbial RNA-sequencing) 50,88 . Twenty-one studies did not report dietary data for all the participants 36,39,102,104,106,111,113,115117,119,121,74,123,76,79,80,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations